Comparison of Wood Based Energy Related Policies in Russia and Finland: Case Study of the Republic of Karelia and North Karelia - Muñoz, Isabel; Goltsev, Vadim (Finnish Forest Research Institute, 2012)
The present analysis reports on key policy documents regarding wood based energy in Russia and Fin- land and their development in regional plans. A comparison of key policy and legislative documents regarding wood based energy is developed. Furthermore, the study highlights the impact of climate and energy policies developed at international and community level on the selected countries performances.The results suggest that international and community treaties have had a positive effect on wood based energy policies in both countries. However, the measures adopted at national level are developing at a different pace. While Finland has a wide variety of policy documents promoting wood based energy, more specific policies and measures are needed on the Russian side.Regarding regional policies performance, wood based energy is gaining importance. The development of renewable energy from wood is seen as positive in both the Republic of Karelia (Russia) and the province of North Karelia (Finland). Nevertheless, in Russia, more supportive measures from the State and attracting investors are crucial to strengthen the wood based energy sector within the Republic of Karelia.
Layout: Sisko Salminen, Metla
Keywords: climate change; Finland; policies; Russia; wood based energy